Knowledge and perception of venous thromboembolism among antenatal women in Hospital Universiti Sains Malaysia - Fen, Lim Suk (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Antenatal women have a high risk of developing venous thromboembolism as pregnancy raises to a condition where a blood clot can form easily. In Malaysia, obstetrics embolism is the second-highest leading cause of maternal mortality in 2018 and there is a lack of published data to assess the knowledge and perception of venous thromboembolism among antenatal women. This research aimed to determine the level of knowledge and perception of antenatal women as well as to determine the association of demographic characteristics with the level of knowledge of venous thromboembolism. A crosssectional study was conducted in the obstetrics ward and Obstetrics and Gynaecology Clinic of Hospital Universiti Sains Malaysia from January to February 2021. A total of 143 participants was conveniently selected and data were collected using a structured self-administered questionnaire adopted from Jarab et al., (2019). Chi-square test was used to determine the association between demographic characteristics and level of knowledge. Results showed the level of knowledge and perception of venous thromboembolism among antenatal women was low (n=137, 95.8%) and the majority have positive perception (n= 142, 99.3%). The result also showed a statistically significant association between demographic characteristics of the field of occupation (pvalue = 0.003) and monthly household income (p-value < 0.001) with the level of knowledge. In conclusion, knowledge of venous thromboembolism among antenatal women was low and have a positive perception. Antenatal women who worked in the field of healthcare and high monthly household income had a high level of knowledge. Health education on women regarding venous thromboembolism should be carried out by constructing a national public education campaign aiming to improve awareness of women regarding this disease during pregnancy and postpartum.